A systematic review of guidelines on screening for celiac disease in children with thyroid disease and vice versa - D’Ambrosio, Talia; Bianchin, Silvia; Gastaldi, Roberto; Zampatti, Noemi; Biagioli, Valentina; Naim, Alessandro; Malerba, Federica; Gandullia, Paolo; Maghnie, Mohamad; Crocco, Marco (Frontiers in Pediatrics, 2025)
IntroductionAutoimmune thyroid diseases (ATD) are the most prevalent autoimmune disorders associated with celiac disease (CD). Both conditions can often be detected through serological screening in asymptomatic patients over several years. Various guidelines for screening thyroid disease (TD) are available in children with CD and vice versa.MethodsWe conducted a systematic review to identify the most recent and relevant guidelines, comparing their recommendations to analyze key differences and suggesting a practical clinical approach.ResultsOut of 1,294 articles reviewed, we identified 20 guidelines published between January 2013 and January 2024. These guidelines, primarily from gastroenterological organizations in Europe and North America, recommend different timings and methods for screening the co-occurrence of these diseases, both at diagnosis and during follow up. Some guidelines recommend only clinical follow-up without routine serological screening. There is limited consensus on screening for TD [using thyroid-stimulating hormone test (TSH)] in asymptomatic children newly diagnosed with CD, and even less agreement on screening for CD [using anti-transglutaminase antibodies (tTG) immunoglobulin A (IgA) test and total IgA] in children newly diagnosed with TD. No standardized procedures exist for managing patients with isolated low tTG and human leukocyte antigen (HLA) genotyping is rarely recommended as a first- line screening method.DiscussionOver the past decade, there has been a growing recognition of the importance of identifying children with co-occurrence of CD and TD who could benefit from early treatment, even in the absence of symptoms. However, international guidelines still show a lack of consensus regarding screening for these frequently associated autoimmune diseases, with notable differences in the use of HLA testing and follow-up protocols.